WEB-BASED BEAUTY SALON ORDERING INFORMATION SYSTEM AT DREAM SKIN AESTHETIC - Halilatul Muallafa; Yunita, Irma; Fatah, Zaehol (Jurnal Teknik Informatika (Jutif), 2024)
Dream Skin Aesthetic is a business that operates in the field of beauty services, especially facial treatments such as laser, basic facial, facial detox, spot peeling, acne peeling, etc. These service activities are carried out offline, which often causes long queues and inconvenience for customers such as services and maintenance services in general. In offline services, a weakness has been found which has been a problem for the owner all this time, namely the customer queques piling up when they want to carry out maintenance because they wait too long because these customers come directly to the place and don’t do it. Order in advance via telephone or WhatsApp. To overcome this problem, an online ordering and service management system was developed using the waterfall software development method. This system is designed to make it easier for users to access information, place orders and transact online. Apart from that, this system also helps the Dream Skin Aesthetic salon in managing customer data and order data more effectively and efficiently. This research resulted in a good system, as evidenced by reduced queues, increased customer satisfaction based on surveys, and increased salon operational efficiency as seen from more organized management data.